Attitude towards Older People According to Sociodemographic and Educational Variables in Students of a Chilean University - Yanez-Yanez, Rodrigo; Antonia Parra-Rizo, Maria; Mc- Ardle Draguicevic, Nelson Fabian; Valdes-Valdes, Nathalie; Rojas, Gabriel A.; Gamin, Leslith; Lorca, Paulina; Acevedo-Carrizo, Francisca; Zapata-Lamana, Rafael; Diaz-Vargas, Caterin; Cigarroa, Igor (My University, 2022)
Current evidence suggests that attitude towards older people may be associated with sociodemographic and educational variables; hence, a positive attitude towards older people is key when training new university professionals. However, there is little evidence of this association in Chilean university students. The objective was to analyze students from a Chilean university's attitudes towards older people, according to sociodemographic and educational variables. Analytical and cross-sectional study; 515 students from a Chilean university were consulted online about their attitude towards older people using Kogan's Attitudes towards Old People scale. Additionally, sociodemographic and educational variables were recorded. The average score for positive attitude was 70.8 (+/- 9.7), while the negative attitude score was 68.3 (+/- 11.6). The total score was 139.1 (+/- 16.6). Mostly, university students perceive themselves with a low-level positive attitude (61.2%). Additionally, older university students (26-42 years old); women; Chileans; students of law, speech therapy, and occupational therapy; students in their final years of the programs; and those who had training in older people outside the university have a more positive attitude towards older people. In Conclusion, a profile of sociodemographic and educational characteristics of students with a lower and higher attitude towards older age was investigated. These results are relevant since the way of seeing the aging process could regulate the training of future professionals and consequently generate changes in dealing with older people. Young people's perception of ageing would affect the treatment and incorporation of the older people in society and the adaptation of policies in this age group.
Keywords: attitude; aging; old age; higher education; ageism; old ageism; stereotypes; prejudices; older people